Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have two questions. The definition I learned defined a laurents for a function analytic in some annalus? I guess this question is asking annali centered at $1$? How do I determine all the annali?

Also, is there a quicker way to find coefficients $a_n$ of the laurent series without applying the definition directly (i.e $a_n = 1/2\pi i \int f(\zeta)/(\zeta - 1?)^{n+1} d\zeta$)

share|cite|improve this question

The function has two simple poles at $z=0$ and $z=1$. If we want the Laurent series of $f$ at $1$ then we have to consider two annuli, $0<\left|z-1\right|<1$ and $1<\left|z-1\right|$. For the first annulus, i.e. $0<\left|z-1\right|<1$ we have that \begin{equation}\frac{1}{z(z-1)}=\frac{1}{z-1}\frac{1}{1+(z-1)}=\frac{1}{z-1}\sum_{n=0}^{\infty}(-1)^n(z-1)^n=\sum_{n=-1}^{\infty}(-1)^{n+1}(z-1)^n \end{equation} For the second annulus $1<\left|z-1\right|$, \begin{equation}\frac{1}{z(z-1)}=\frac{1}{(z-1)^2}\frac{1}{1+\frac{1}{z-1}}=\frac{1}{(z-1)^2}\sum_{n=0}^{\infty}(-1)^n\frac{1}{(z-1)^n}=\sum_{-\infty}^{n=-2}(-1)^{n}(z-1)^n \end{equation} In both cases we used that \begin{equation}\frac{1}{1+\zeta}=\frac{1}{1-(-\zeta)}=\sum_{n=0}^{\infty}(-\zeta)^n=\sum_{n=0}^{\infty}(-1)^{n}\zeta^n \end{equation} for $\left|\zeta\right|<1$.

Final notes: When you are asked to compute all Laurent series at a given point $z_0$ you first determine the non-removable singularities of the function. You choose your annuli $\left\{z\in \mathbb{C}:r<\left|z-z_0\right|<R\right\}$ ($0\le r<R\le +\infty$) so that your function has no non-removable singularites in them. Then you use the geometric series \begin{equation}\frac{1}{1-\zeta}=\sum_{n=0}^{\infty}\zeta^n \end{equation} for $\left|\zeta\right|<1$ or use the Taylor series to expand the other functions (exponential, trigonometric etc.) that may be involved. Your goal is to have only terms of the form $c_n(z-z_0)^n$ in your expression. If you find one Laurent series at an annuli then it is unique. Finally, we rarely use the integral formula of $a_n$ for computations. I think this should be of help Laurent Series

share|cite|improve this answer

Here is a related problem. First notice that $z=1$ is a simple pole of the function. The residue of the function at $z=1$, which is the coefficient of $(z-1)^{-1}$ in the Laurent series, is $1$ and you will see this from the series once it is derived. Here is how you compute the series

$$ \frac{1}{z^2-z}=\frac{1}{(z-1)z}=\frac{ 1 }{(z-1)(1+(z-1))}$$

$$=\frac{1}{z-1}(1-(z-1)+(z-1)^2-(z-1)^3-\dots) $$

$$ \frac{1}{z-1}-1+(z-1)-(z-1)^2+\dots $$

$$ = \frac{1}{z-1} - \sum_{k=0}^{\infty}(-1)^k(z-1)^k, \quad 0<|z-1|<1 $$

You can see from the above series that the coefficient of $(z-1)^{-1}$ is one as we said in the beginning. For the other series, $|z-1|>1$, we have

$$ \frac{1}{z^2-z}=\frac{1}{z(z-1)} = \frac{1}{(z-1)((z-1)+1)} = \frac{1}{(z-1)^2(1+\frac{1}{(z-1)})} $$

$$ =\frac{1}{(z-1)^2}( 1-(z-1)^{-1}+(z-1)^{-2}+\dots )$$

$$ =\frac{1}{(z-1)^2}+\sum_{k=0}^{\infty}(z-1)^{-k}, \quad |z-1|>1. $$

Note that, the series

$$ \frac{1}{1+x}=1-x+x^2-x^3+\dots\,, $$

was used in the above derivation.

share|cite|improve this answer
Note the "all" part of the question. You're missing one. – WimC Dec 1 '12 at 7:32
@WimC: Thanks for the reminder. – Mhenni Benghorbal Dec 4 '12 at 3:36

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.